Fluorescence imaging of a potential diagnostic biomarker for breast cancer cells using a peptide-functionalized fluorogenic 2D material. Issue 88 (17th October 2019) - Dou, Wei-Tao; Liu, Li-Fang; Gao, Jie; Zang, Yi; Chen, Guo-Rong; Field, Robert A.; James, Tony D.; Li, Jia; He, Xiao-Peng
Abstract : A fluorogenic 2D material has been developed for the imaging of PROCR, a potential biomarker for triple-negative breast cancer. Abstract : Protein C receptor (PROCR) is a recently discovered transmembrane biomarker for several tissue stem cells and is highly expressed in triple-negative breast cancer (TNBC) patient-derived xenografts. Herein, to enrich the toolbox for the biochemical evaluation of PROCR, we have developed a peptide-functionalized fluorogenic 2D material based on the self-assembly between a fluorescent peptide probe and thin-layer molybdenum disulfide. The material developed was suitable for the sensitive detection of PROCR recombinant protein in buffer solution and the fluorescence imaging of TNBC cells that express high levels of PROCR.